The effect of proposed exercises to develop sensory-motor perception in decision-making regarding the performance of individual and group rapid attack skills for handball goalkeepers - Hussein, Asst.L.Mustafa Muhammad (Sulaimani Journal for Humanities, 2026)
The field of sports is witnessing remarkable development in all games, whether individual or team sports. This development did not come about by mere chance, but rather through the interest of those in charge of this field and their attempts to find modern theories and employ them in the best and correct scientific ways and methods to reach the highest level of performance and achieve accomplishment. Sensory-motor perception plays an important and fundamental role in the process of motor coordination during performance through the sense of muscular effort or the sense of resistance or speed of movement. Moreover, all balance and jumping movements require us to have a high ability for sensory-motor perception in terms of many variables such as sensory perception of distance, time, force and direction. Developing a goalkeeper's perception helps them make the right decision for the appropriate motor response during a match, as well as making timely decisions to perform, leading to successful motor performance. Decision-making is therefore one of the most important factors in successful motor performance, as the performance is determined by variables such as timing, force, speed, and direction. Any flaw in decision-making regarding these variables will hinder successful motor performance. Thus, one of the requirements for a handball goalkeeper is the ability to make the right and accurate decision regarding the nature of the performance during a match to achieve the objective. This includes speed in decision-making, as the time available for a handball goalkeeper to make a decision during a match is very short. Experience, practice, the accuracy of the player's perceptual information, and other factors influence the accuracy and speed of decision-making. The importance of this research lies in developing new exercises to enhance sensory-motor perception and the decision-making process, aiming to bring the goalkeeper to the best level of performance. The skills of (quick individual and group attacks) and quick passing are among the most important offensive skills in handball due to their significant role in achieving a good result in a match.